2011
DOI: 10.2527/jas.2010-3597
|View full text |Cite
|
Sign up to set email alerts
|

Circulating ghrelin and leptin concentrations and growth hormone secretagogue receptor abundance in liver, muscle, and adipose tissue of beef cattle exhibiting differences in composition of gain

Abstract: Data from species other than cattle indicate that ghrelin and GH secretagogue receptor (GHS-R) could play a key role in fat deposition, energy homeostasis, or glucose metabolism by directly affecting liver and adipose tissue metabolism. Beef steers (n = 72) were used to test the hypothesis that plasma ghrelin and leptin concentrations and abundance of the GHS-R in liver, muscle, and adipose tissues differ in steers exhibiting differences in composition of gain. At trial initiation (d 0), 8 steers were slaughte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…Ghrelin concentration has been associated with energy intake/partitioning in ruminants (Jennings et al, 2011). However, current data does not discern whether ghrelin is a true regulator of DM intake.…”
Section: Endocrine Systemmentioning
confidence: 60%
See 1 more Smart Citation
“…Ghrelin concentration has been associated with energy intake/partitioning in ruminants (Jennings et al, 2011). However, current data does not discern whether ghrelin is a true regulator of DM intake.…”
Section: Endocrine Systemmentioning
confidence: 60%
“…However, this was dependent on the time when plasma was sampled in relation to the feeding process, because this association was not found in studies with multiple samplings (Foote et al, 2016). Moreover, if ghrelin affects feed intake and animal growth, it may depend on the physiological state and type of diet (Jennings et al, 2011;Foote et al, 2014). The role of glucose-dependent insulinotropic polypeptide on beef cattle has not been studied in detail with no available data evaluating its role on feed efficiency.…”
Section: Endocrine Systemmentioning
confidence: 99%
“…However, pulses of ghrelin release are not evident in ad libitum fed sheep (Sugino et al, 2002b); therefore, a single measure of ghrelin concentrations are likely sufficient to determine associations with DMI and efficiency. Additionally, Jennings et al (2011) have shown that ghrelin concentrations can change over the feeding period and are affected by composition of BW gain. Future research may warrant further investigation of changes of ghrelin concentrations over the finishing period and association with DMI and efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…It is still unclear, however, if acyl ghrelin is associated with body composition, or composition of BW gain. Foote, et al [8] showed no correlation of acyl ghrelin with carcass composition; however, Jennings, et al [16] showed that cattle accreting fat at a greater rate also had greater acyl ghrelin concentrations, which would concur with rodent literature [3,6,23].…”
Section: Discussionmentioning
confidence: 92%
“…In the Foote, et al [8] study, ghrelin was measured after the completion of the DMI measurement period, indicating the association of ghrelin with DMI could be reflective of previous feed intake; however it is unclear how ghrelin concentrations change over time. Jennings, et al [16] showed that acyl-ghrelin concentrations increase with age and/or body fatness in beef steers, but the change was dependent on composition of growth, where cattle accreting more fat had greater acyl-ghrelin concentrations.…”
Section: Discussionmentioning
confidence: 99%